Reconfiguring Political Islam: A Discursive Tradition Approach (American Journal of Islam and Society, 2025)
This article reconceptualizes Political Islam through the analytic lens of discursive tradition, restructured within the framework of social configurations. Departing from essentialist, universalist, nominalist, and reductionist readings, the study foregrounds the epistemological contingencies and internal pluralities that characterize Political Islam as a historically situated and discursively constructed phenomenon. Rather than treating political Islam as a fixed ideological project or a transhistorical expression of Islamic governance, the article theorizes it as a dynamic and contested field in which diverse actors articulate Islamic categories within distinct configurations shaped by contextual transformations, historical ruptures, institutional dislocations, regimes of reasoning, and so on. Drawing on Talal Asad’s notion of discursive tradition, the analysis reconstructs its scope through the concept of social configurations, which enables a multilayered reading of Political Islam across three analytical levels: conditions of possibility, categorical and discursive formation, and social objectification. This theoretical reconstruction clarifies how Islamist discourses emerge not from doctrinal continuity alone, but through strategic negotiations over core issues such as temporality, authority, power, and legitimacy. Through comparative and context-sensitive examination of various Islamist traditions—from reformist to revolutionary, nationalist to transnational, moderate to militant—the article shows how Political Islam operates through a grammar of differentiation and reconfiguration within the broader Islamic tradition. The resulting framework not only situates Political Islam within shifting social terrains, but also offers an epistemological intervention into its interpretation as a plural, indeterminate, and generative discursive tradition.